An Integrated Company-Wide Management System Combining Lean Six Sigma with Process Improvement - Salah, Souraj; Rahim, Abdur (Springer International Publishing : Imprint: Springer, 2019)
This book offers a comprehensive guide to implementing a company-wide management system (CWMS), utilising up-to-date methodologies of lean-six sigma in order to achieve high levels of business excellence. It builds the foundation for quality and continuous improvement, which can be implemented in any organization. The book begins with an introduction to and an overview of CWMSs, and reviews the existing literature on various management systems. It then discusses the integration and implementation of lean-six sigma in supply chain management. The integration approach presented highlights the link between the existing management systems and shows how continuous improvement methodologies are incorporated. The book then examines the components of CWMS, comparing them to other systems. It also explores Kano-based six sigma and concludes with further recommendations for reading. This book covers five management systems integrated into one novel approach that can be followed by organizations wishing to achieve quality and business excellence. Covering lean-six sigma - an essential element of management systems - it is a valuable resource for practitioners and academics alike. .